О фразеологических инновациях в речи детей (на материале русского языка) - Ратайчик, Кристина (SlavVaria, 2022)
About phraseological innovations in the children’s language (based on the Russian language). The aim of the article is to analyze phraseological innovations in the children’s language. The analysis is carried out on the mate-rial of the statements of young Russians, drawn from the children’s language dictionary. The methods of structural analysis, semantic analysis, and selection of research material from the dictionary are the main ones used in the article. As a result of the study, four main types of phraseological innovations in the child’s language were distinguished, i.e. structural, structural-semantic, seman-tic innovations and, as a special group, children’s phraseological neologisms. Thus, the presence of phraseological units in the child’s language is proved.